Ethnic identity and perceptions of the police in Turkey: the case of Kurds and Turks - Sahin, Osman (Policing and society, 2019)
Drawing on the literature on minorities’ and ethnic groups’ perceptions of the police, this article investigates the differences between Kurds and Turks in terms of their perceptions of the police in Turkey. We conducted survey research using a nationally representative sample of 1804 people. Multivariate regression analysis revealed that Kurds in Turkey have a more negative perception of the police than Turks, regardless of their gender, education, income, party affiliation, and sectarian identity. It is concluded that the historical relationship between Kurds and the Turkish state has had a decisive effect on how Kurds perceive the police.